1966
DOI: 10.1021/bi00875a020
|View full text |Cite
|
Sign up to set email alerts
|

Transcortin. A Corticosteroid-Binding Protein of Plasma. IX. Isolation and Characterization*

Abstract: Plasma from male subjects with cancer of the prostate, who were receiving diethylstilbestrol treatment, was fractionated successively on columns of diethylaminoethylcellulose, Sephadex G-25, hydroxylapatite, and Sephadex G-75. Transcortin was detected

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

1969
1969
1989
1989

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 17 publications
(21 reference statements)
1
8
0
Order By: Relevance
“…All chromatographic steps were performed at 6°. DEAE-cellulose chromatography and subsequent desalting on Sephadex G-25 were performed as previously described (Slaunwhite et al, 1966). The resin was equilibrated with starting buffer which was 0.025 m in NaCl and 0.015 m in NaH2P04 at pH 5.0.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All chromatographic steps were performed at 6°. DEAE-cellulose chromatography and subsequent desalting on Sephadex G-25 were performed as previously described (Slaunwhite et al, 1966). The resin was equilibrated with starting buffer which was 0.025 m in NaCl and 0.015 m in NaH2P04 at pH 5.0.…”
Section: Methodsmentioning
confidence: 99%
“…The molecular weight of human transcortin prepared in the present study was determined as previously described (Slaunwhite et al, 1966).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CBG was first isolated from human plasma by Seal and Doe [14] and later by Slaunwhite et al [15] and Muldoon and Westphal [10], The reported molecular weights range from 49,000 to 58,000 daltons [1,6,8,10,15]. Approximately 30% of this weight is carbohydrate, with varia tion in glycosylation partly responsible for the apparent molecular weight heter ogeneity [2,10,17].…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that some component which is present in the in vivo system is absent from the in vitro system . That this component may be a plasma protein is suggested by the facts that : a) cortisone binds selectively to a human plasma protein (8,11), and b) the perfusion of whole rat liver with medium containing cortisone produces little induction of gluconeogenic enzymes, whereas the addition of whole rat blood to such a perfusion system produces a marked induction (1) . It should also be noted that shortly after in vivo administration the hormone is found bound to rat liver histone (12) .…”
Section: Introductionmentioning
confidence: 99%